Homer's Iliad – A Social Network Analytic Approach. Issue 1 (March 2015) - Kydros, Dimitrios; Notopoulos, Panagiotis; Exarchos, Georgios
Abstract : In this paper we provide some insights in Homer's Iliad from the perspective of social network analysis. We use the original text and other public available data to create a social network (i.e. a graph) that comprises of all actors in the Iliad together with their interactions. We present some visualizations of these data and discuss concepts like connectivity, connected components and groupings. Furthermore, we calculate some well-established metrics, coming from social network analysis in this social network and discuss the numerical results. These results indicate that the Iliadic network is a small-world network, rather dissasortative and relatively easy to disconnect.